F(1) = 2
f(2) = 3f(1) = 3(2) = 6
f(3) = 3f(2) = 3(6) = 18 (A)
Answer: the answer is c
Step-by-step explanation:
The verbal expression for the mathematical expression 5(x - 4) + 2 is the number 5 times the difference between an unknown x and the number 4 and plus 2.
<h3>What is an expression?</h3>
It is defined as the combination of constants and variables with mathematical operators.
It is given that a mathematical expression as below:
= 5(x - 4) + 2
Here x is the unknown number
The number
Number 5 times the difference between an unknown x and number 4 and plus 2
Thus, the verbal expression for the mathematical expression 5(x - 4) + 2 is number 5 times the difference between an unknown x and number 4 and plus 2.
Learn more about the expression here:
brainly.com/question/14083225
#SPJ1
Answer:
i dont know toooo pls answer it fast......................................
Step-by-step explanation:
i need it..........................
You have two triangles, ADC and ABC.
Sides AD and AB are congruent.
Sides DC and BC are congruent.
Side AC is congruent to itself.
By SSS, triangles ADC and ABC are congruent.
Corresponding parts of congruent triangles are congruent.
That means that angles DAC and BAC are congruent.
Angles DCA and BCA are congruent.
Since m<DAC = 32, then m<BAC = 32
Since m<DCA = 41, then m<BCA = 41.
Now you know the measures of two angles of triangle ABC.
The measures of the interior angles of a triangle add to 180.
You can find the measure of angle B.
m<BAC + m<B + m<BCA = 180
32 + m<B + 41 = 180
m<B + 73 = 180
m<B = 107